Simple and Rapid Quantification of Total Carotenoids in Lyophilized Apricots (Prunus armeniaca L.) by Means of Reflectance Colorimetry and Photoacoustic Spectroscopy - Gitta Ficzek (Food Technology and Biotechnology, 2013)
Photoacoustic spectroscopy (PAS) and reflectance colorimetry are suggested as new tools for the analysis of total carotenoids in lyophilized apricot powders. The data obtained by these two techniques from seven apricot cultivars were compared to those acquired by spectrophotometry and high-performance liquid chromatography (HPLC). Best correlations were found between the total carotenoid (TC) content (obtained by VIS spectrophotometry: 1.2–3.4 mg per 100 g of fresh mass) and colorimetric index a* (a* represents the redness of the investigated sample), as well as either argon-ion laser- or xenon-lamp-based PAS. In all three cases linear correlations were comparable. However, according to the sensitivity and precision data, expressed via limit of detection (LOD) and measurement repeatability, the Xe-lamp-based PAS is a preferred approach, followed by colorimetric index a* and Ar-ion laser PAS. Both PAS methods exhibit practically the same Pearson's correlation coefficient (R=0.987 and R=0.991) values. Nevertheless, residual sum of squares (RSS) and residual standard deviation of the linear regression (sy/x) differ markedly. For Xe-lamp-based PAS these parameters were much lower than in the case of Ar-ion laser PAS. Likewise, analysis imprecision amounted to relative standard deviation (RSD) of 1–3 % for Xe-lamp PAS and 2–6 % for Ar-ion laser PAS. On the other hand, as expected, the calibration sensitivity achieved for the PAS signal induced by an Ar-ion laser at 481 nm was substantially higher than that of a Xe-lamp at 470 nm. Nevertheless, according to much lower sy/x, the corresponding LOD for Xe-lamp PAS was still two times lower than that of Ar-ion-based laser PAS (0.59 vs. 1.10 mg per 100 g). Unlike this, Ar-ion laser PAS showed more favourable instrumental precision and standard error of the weighed mean when compared to the Xe-lamp PAS (0.1–0.6 and 0.1–0.3 % vs. 0.5–8.0 and 0.4–1.7 %, respectively). As far as colorimetric indices are concerned, only a* proved to be analytically useful; excellent R but rather modest RSS and sy/x resulted in LOD value of 0.70 mg per 100 g and acceptable analysis imprecision of up to 3 %. The outcome of this research provides sufficient amount of evidence that analytical methods such as reflectance colorimetry and PAS without the use of any chemicals are feasible for reliable quantification of total carotenoids in freeze-dried apricot homogenates.